Intracerebral Infusion of Antisense Oligonucleotides Into Prion-infected Mice - Karah Nazor Friberg; Gene Hung; Ed Wancewicz; Kurt Giles; Chris Black; Sue Freier; Frank Bennett; Stephen J DeArmond; Yevgeniy Freyman; Pierre Lessard; Sina Ghaemmaghami; Stanley B Prusiner (Elsevier, 2012)
Mice deficient for the cellular prion protein (PrPC) do not develop prion disease; accordingly, gene-based strategies to diminish PrPC expression are of interest. We synthesized a series of chemically modified antisense oligonucleotides (ASOs) targeted against mouse Prnp messenger RNA (mRNA) and identified those that were most effective in decreasing PrPC expression. Those ASOs were also evaluated in scrapie-infected cultured cells (ScN2a) for their efficacy in diminishing the levels of the disease-causing prion protein (PrPSc). When the optimal ASO was infused intracerebrally into FVB mice over a 14-day period beginning 1 day after infection with the Rocky Mountain Laboratory (RML) strain of mouse prions, a prolongation of the incubation period of almost 2 months was observed. Whether ASOs can be used to develop an effective therapy for patients dying of Creutzfeldt-Jakob disease remains to be established.